Spillover effects of children's political status on elderly parents' health in China. Issue 11 (5th September 2018) - Zhao, Xin; Zhou, Yi; Tan, Huaqing; Lin, Haoxiang
Abstract : Background: Due to the sustained increases in life expectancy over the past half century, the elderly today will receive supports from their children for a longer period than ever before. Therefore, understanding the spillover effects of children's socioeconomic status on parents' health becomes increasingly important for both scholars and policy makers. Methods: The Ordinary Least Squares regression is applied to the China Health and Retirement Longitudinal Study 2011, a national representative dataset including approximately 10 000 households and 17 600 middle-aged and elderly respondents. The Sobel test is used to examine the mediation role of social integration. Results: The elderly who have a cadre child reported better health (coefficient=0.1347; 95% CI 0.067 to 0.202), had fewer activities of daily living (ADLs) limitations (coefficient=−0.1289; 95% CI −0.216 to −0.042) and were more socially integrated (coefficient=0.2321; 95% CI 0.103 to 0.361). Such effects are mainly driven by the parents of higher-ranking cadres. For the parents of higher ranking cadres, the Sobel test suggests that 12.6% of the total effects on self-reported health and 21.9% of the total effects on ADL limitations are mediated by the increase in parents' social integration. Conclusion: The findings suggest positive spillover effects of children's political status on parents' health. The benefits of having a cadre child are at least equivalent to the rural–urban gap in health and even stronger for the parents of higher ranking cadres. One potential explanation for such spillover effects is that a child's political status can improve parents' community involvement and social interactions.